Effect of angiotensin-converting enzyme tag single nucleotide polymorphisms on the outcome of patients with traumatic brain injury. Issue 10 (October 2015) - Dardiotis, Efthimios; Paterakis, Konstantinos; Siokas, Vasileios; Tsivgoulis, Georgios; Dardioti, Maria; Grigoriadis, Savas; Simeonidou, Constantina; Komnos, Apostolos; Kapsalaki, Eftychia; Fountas, Kostas; Hadjigeorgiou, Georgios M.
<x xml:space="preserve">Abstract</x> Background Genetic variants appear to influence, at least to some degree, the extent of brain injury and the clinical outcome of patients who have sustained a traumatic brain injury (TBI). Angiotensin-converting enzyme (ACE) is a zinc metallopeptidase that is implicated in the regulation of blood pressure and cerebral circulation. ACE gene polymorphisms were found to regulate serum ACE enzyme activity. Objective The present study aimed to investigate possible influence of ACE gene region variants on patients' outcome after TBI. Patients and methods In total, 363 TBI patients prospectively enrolled in the study were genotyped for five tag single nucleotide polymorphisms (SNPs) across the ACE gene. Using logistic regression analyses, tag SNPs and their constructed haplotypes were tested for associations with 6-month Glasgow Outcome Scale scores, after adjustment for age, sex, Glasgow Coma Scale scores at admission, and the presence of a hemorrhagic event in the initial computed tomography scan. Results Significant effects on TBI outcome were found for three neighboring tag SNPs in the codominant (genotypic) model of inheritance [rs4461142: odds ratio (OR) 0.26, 95% confidence interval (CI) 0.12–0.57, P=0.0001; rs7221780: OR 2.67, 95% CI 1.25–5.72, P=0.0003; and rs8066276: OR 3.82, 95% CI 1.80–8.13, P=0.0002; for the heterozygous variants compared with the common alleles]. None of the constructed common tag SNPs haplotypes was associated with TBI outcome. Conclusion The present study provides evidence of the possible influence of genetic variations in a specific region of the ACE gene on the outcome of TBI patients. This association may have pharmacogenetic implications in identifying those TBI patients who may benefit from ACE inhibition.